2000
DOI: 10.1074/jbc.m000875200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Movement in Niemann-Pick Type C Cells and in Cells Treated with Amphiphiles

Abstract: Cholesterol accumulates to massive levels in cells from Niemann-Pick type C (NP-C) patients and in cells treated with class 2 amphiphiles that mimic NP-C disease. This behavior has been attributed to the failure of cholesterol released from ingested low density lipoproteins to exit the lysosomes. However, we now show that the rate of movement of cholesterol from lysosomes to plasma membranes in NP-C cells is at least as great as normal, as was also found previously for amphiphiletreated cells. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
189
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(207 citation statements)
references
References 51 publications
18
189
0
Order By: Relevance
“…Proteins were solubilized with CHAPS, separated by size exclusion chromatography, and the elution profile of Bax was analyzed by immunoblotting. For each condition, even-numbered fractions were loaded on two separate gels; a short exposure time was chosen for the low molecular weight fractions (30-44), and a longer one for the high molecular weight fractions (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and its sensitivity to trypsin digestion were analyzed by immunoblotting. The presence of tBid was required for the recruitment of Bax to liposomes and led to the appearance of a Tr-Bax fragment (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteins were solubilized with CHAPS, separated by size exclusion chromatography, and the elution profile of Bax was analyzed by immunoblotting. For each condition, even-numbered fractions were loaded on two separate gels; a short exposure time was chosen for the low molecular weight fractions (30-44), and a longer one for the high molecular weight fractions (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and its sensitivity to trypsin digestion were analyzed by immunoblotting. The presence of tBid was required for the recruitment of Bax to liposomes and led to the appearance of a Tr-Bax fragment (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…U18666A is a drug that induces intracellular cholesterol accumulation, an abnormality that is encountered in Niemann-Pick Type C1 disease. It interferes with the trafficking of cholesterol, causing its increase in late endosomes/lysosomes, 23,24 and inhibits its neosynthesis in the ER. 25 A recent study reported the accumulation of cholesterol in the mitochondria of neurons isolated from an Niemann-Pick Type C1 mouse model, 26 raising the possibility that U18666A might also increase mitochondrial cholesterol content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main features of the NPC phenotype can be mimicked by cultured cells exposed to a variety of reagents called class 2 amphiphiles, such as U18666A (17). It is now believed that these reagents act directly on the NPC1 protein (18). Based on these facts, we hypothesized that intracellular A␤ metabolism might be changed in these cholesterol-perturbed cells.…”
mentioning
confidence: 99%
“…The increased cholesterol impaired insulin signaling and was restored following cholesterol depletion (24). In other studies cholesterol levels have been reported to be increased, decreased, or unchanged (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 88%